STUDI TENTANG KINERJA PEGAWAI DALAM PELAYANAN ADMINISTRASI DI DESA TANI HARAPAN KABUPATEN KUTAI KARTANEGARA - Yusriani, Nanik Pujiastuti, dan Marsuq (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2022)
Purpose of this research isFor knowing Performance Employee in ServiceAdministration and For knowing Factor supporter and blocker Performance Employee inService Administration in the Villagefarmer Hopedistricts Kutai Kartanegara.Research conducted is qualitative explored and deepened from phenomenon socialor environment social which consists of on perpetrator, event, place and time , employeevery satisfactory.